Testamentary Inheritance in Comparative Law. A Comparative View of Testamentary Practices and Legal Frameworks in Italy and Latin America - Buțureanu, Andreea (Journal of Legal Studies, 2021)
The practice of making wills is as diverse as it is old. While the legislation in some cultures favors certain principles, others emphasize distinct precepts, all of which are guided in the background by the different cultural views about family and the importance attributed to the surviving spouse. Since the practice of testamentary inheritance is based on the desire to provide care to those left behind by the testator, and not in a few cases, in the absence of a constant income that he used to provide, it is important to identify the logic after which each legislator decides who are vulnerable people and which part of the successoral mass should be attributed to them. In the context of societal change in which the family no longer has the same definitions, the present study conducts a comparative analysis of testamentary practices and legal frameworks in Italy and Latin America in an effort to identify both the common elements that define these two Latin geographical areas, as well as their particularities. This analysis is relevant to the established literature in the field of inheritances by capturing the characteristics of two legal systems that have not received the necessary academic attention.